Antiviral and Antiproliferative Potential of Marine Organisms From the Yucatan Peninsula, Mexico - Pech-Puch, Dawrin; Berastegui-Cabrera, Judith; Pérez-Povedano, Mar; Villegas-Hernández, Harold; Guillén-Hernández, Sergio; Cautain, Bastien; Reyes, Fernando; Pachón, Jerónimo; Gómez, Patricia; Rodríguez, Jaime; Jiménez, Carlos; Sánchez-Céspedes, Javier (Frontiers in Marine Science, 2020)
Viral infections are one of the main human health problems in recent decades and the cancer remains one of the most lethal diseases worldwide. The development of new antiviral drugs for the treatment of human adenovirus (HAdV) infections continues to be a challenging goal for medicinal chemistry. There is no specific antiviral drug approved to treat infections caused by HAdV so far and the off-label treatments currently available show great variability in their effectiveness. In relation to cancer, most of the available drugs are designed to act on specific targets by altering the activity of involved transporters and genes. Taking into account the high antiviral and antiproliferative activity against tumour cell lines displayed by some marine natural products reported in the literature, sixty five marine organisms we selected: 51 sponges (Porifera), 13 ascidians (Chordata) and 1 gorgonian (Cnidaria), collected from Yucatan Peninsula, Mexico, to evaluate their antiviral activity against human adenovirus type 5 (HAdV5) and their anticancer properties against five human tumour cell lines, namely human lung carcinoma (A549), human skin melanoma (A2058), hepatocyte carcinoma (HepG2), breast adenocarcinoma (MCF7) and pancreas carcinoma (MiaPaca-2). Eleven extracts displayed anti-HAdV activity being the organic extracts of Dysidea sp., Agelas citrina, Chondrilla sp., Spongia tubulifera and Monanchora arbuscula the five most active ones. On the other hand, twenty-four extracts showed antiproliferative activity against at least one tumour cell line, being the extracts of the ascidian Eudistoma amanitum and the sponge Haliclona (rhizoniera) curacoensis the most active ones. This work constitutes the first wide antiviral and antiproliferative screening report of extracts from the marine sponges, ascidians, and a gorgonian collected from the Yucatan Peninsula, Mexico.